ASSESSMENT OF BIOCHEMICAL INDICATORS OF ORAL FLUID IN CHILDREN WITH EXCESSIVE BODY WEIGHT WITH THE USE OF THERAPEUTIC AND PREVENTIVE COMPLEX - Tsushko, I.O.; Shnaider, S.A.; Shvartsnau, O.H.; Dieva, T.V.; Pryima, O.A.; Romanova, Yu.H.; Lysenko, T.O. (World of Medicine and Biology, 2022)
The study is devoted to the study of biochemical indicators of the oral fluid of children with major dental diseases against the background of excess body weight in the process of carrying out the developed therapeutic and preventive measures. 48 children aged 15 to 18 took part in the clinical examinations according to the “inclusion/exclusion” criteria. The children were divided into 2 groups (the main group – 25 children and the comparison group – 23 children). In the comparison group, only basic therapy (sanitation of the oral cavity and professional hygiene) was carried out. In addition to the basic therapy, the patients of the main group were prescribed a developed treatment and prevention complex. The use of the developed complex made it possible after 1 year to reduce the activity of the inflammatory process, increase antioxidant and non-specific antimicrobial protection and normalize the microbiocenosis of the oral cavity.